Sand particle produced by unstable perforated wellbore - Samsuri, Ariffin (1994)
The paper presents the results of a laboratory study of the sand particle produced from unstable perforated wellbore. Section of a perforated wellbore were generated and expose to various loads and conclusions were drawn with respect to the produced sand particle during loading process, up to failure of the perforated wellbore structure. The results show that the perforated wellbore may fail during the creation process and sand particles were produced, depending on the perforated wellbore geometry or perforation parameters and rock properties. The sand particles produced were found by sieve analysis to be oversized 500Î¼. Generally, stable perforated wellbore produced less sand particle, therefore minimizing the sand production problems.